Historical Trends in Sweet Corn Plant Density Tolerance Using Era Hybrids (1930–2010s) - Dhaliwal, Daljeet S.; Ainsworth, Elizabeth A.; Williams, Martin M. (Frontiers in Plant Science, 2021)
Over the last six decades, steady improvement in plant density tolerance (PDT) is one of the largest contributors to genetic yield gain in field corn. While recent research indicates PDT in modern sweet corn hybrids could be exploited to improve yield, historical changes in PDT in sweet corn are unknown. The objectives of this study were to: (a) quantify the extent to which PDT has changed since introduction of hybrid sweet corn, and (b) determine the extent to which changes over time in PDT are associated with plant morpho-physiological and ear traits. An era panel was assembled by recreating fifteen sugary1 sweet corn hybrids that were widely used at one time in the US, representing hybrids since the 1930s. Era hybrids were evaluated in field experiments in a randomized complete block design with a split-plot arrangement of treatments, including hybrid as the main factor and density as the split-plot factor. Plant density treatments included ‘Low’ plant density (9,900 plants/ha) free of crowding stress or ‘High’ plant density (79,000 plants/ha) with crowding stress. On average, per-area marketable ear mass (Mt/ha) increased at a rate of 0.8 Mt/ha/decade at High densities, whereas per-plant yield (i.e., kg/plant) remained unchanged over time regardless of the density level. Crate yield, a fresh market metric, improved for modern hybrids. However, processing sweet corn yield metrics like fresh kernel mass and recovery (amount of kernel mass contributing to the fresh ear mass), showed modest or no improvement over time, respectively. Modern sweet corn hybrids tend to have fewer tillers and lower fresh shoot biomass, potentially allowing the use of higher plant density; however, plant architecture alone does not accurately predict PDT of individual hybrids.